PENERAPAN BASE TEN BLOCK SEBAGAI MEDIA DALAM MEMAHAMKAN KONSEP OPERASI BILANGAN BULAT DI KELAS VII - Siti Nur Azizah; Dzurotul Mutimmah; Barep Yohanes; Dewi Wardah (TRANSFORMASI, 2025)
Understanding concepts is a fundamental requirement for every student to be able to apply those concepts in other processes. Base Ten Block is a learning medium used to introduce integers and their operations. This research was conducted in accordance with the problem found in the research area, namely, students’ lack of understanding of the concept of integer operations. Therefore, this study aims to determine the effectiveness of Base Ten Block media in improving students’ understanding of integer operations in grade VII at MTs Sunan Ampel Patoman. The research was conducted using a quantitative approach with a one-group pretest-posttest design. Respondents were 32 seventh-grade students selected using purposive and saturated sampling techniques. The test, a previously validated instrument, was used in data collection. Data were obtained in the form of initial test results (teacher documentation before treatment) and final test results. Data were analyzed using a z-test after determining normality. The analysis results show that the percentage of achievement of the KKTP (qualifying standards) in the final test was higher than in the initial test. Hypothesis testing also showed a significant difference between the test results. Therefore, it can be concluded that the Base Ten Block media is effective in improving understanding of the concept of integer operations. The limited supporting research suggests that this research could be repeated at the junior high school level with different respondents and research areas.